Stressors and Coping Strategies as Perceived among Nursing Students during Related Learning Experience (RLE) - Ridad, Geraldine Sabate; Angintaopan, Haniya; Ayunan, Princess Haniefa Mae; Manalocon, Saipoden (Nurse Media Journal of Nursing, 2024)
Background: Stress in relation to academic studies is identified to be one of the reasons behind suicide cases in higher education institutions around the world. Locally, there is none to less studies that explored this area among nursing students. As stress is inevitable in nursing students’ Related Learning Experience (RLE), recognizing the stressors that affect their quality of RLE is necessary.Purpose: This study aimed to investigate the stressors and coping strategies that nursing students commonly use in managing stress during their RLE and their relationship to each other.Methods: A descriptive correlational research design with total enumeration sampling was employed. A pilot-tested questionnaire was used to gather data from 191 junior and senior nursing students from two nursing schools in Iligan City. Weighted mean, standard deviation, percentages, and Spearman rho were used to analyze the data.Results: The findings show that the "Clinical Instructor" (Mean=3.01) is perceived to cause higher stress among all the intrapersonal and interpersonal stressors identified. Students highly utilize both intrapersonal (Self-Concept Mean=3.75) and interpersonal strategies (Role Function Mean=4.13, Interdependence Mean=3.46) to cope with stress. When students’ clinical “skill confusion” increases, they tend to work less with others (r=-0.259, p=0.000). When “staff nurses” cause them less stress, their use of positive “self-concept” decreases as well (r=0.152, p=0.035). Furthermore, when students are stressed with their “Duty-mates,” they rely more on “physiological” coping mechanisms (r=0.160, p=0.027). When their “clinical instructor” causes them stress, they cope less with “physiological” (r=-0.237, p=0.001) and “interdependence” strategies (r=-0.317, p=0.000).Conclusion:Among all the stressors, clinical instructor causes more stress to the students. The students’ perceived stressors affect their effective use of intra and interpersonal coping strategies. Nurse educators, nursing schools and regulating bodies can consider these results in designing a holistic curriculum and helping students manage stress healthily.